Products of composition operators and volterra-type integral operators from logarithmic bloch spaces into Bloch-type Spaces - Liu, Yongmin (Tamsui Oxford Journal of Mathematical Sciences)
Let be an analytic self-map of the unit disk D, H(D) the space of analytic functions on D and g 2 H(D). The boundedness and compact-ness of the products of composition operators and Volterra-type integral operators from the logarithmic Bloch spaces into the Bloch-type spaces are investigated in this paper.